AN ANALYSIS OF STAFF LOYALTY IN THE HOSPITALITY SECTOR WITH PARTICULAR ATTENTION TO MADHYA PRADESH - Chaurasia, Nikhil; Singh, Kumkum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The tourism sector is one of the most significant sectors globally. Tourism has been given significant importance in almost all states of India. State governments are actively pursuing opportunities to capitalize on their tourist resources and potentials. The tourist sector in Madhya Pradesh plays a crucial part in its economic growth. The individuals employed in this business are the fundamental pillar supporting its success. Therefore, the implementation of robust HRD processes is essential for their growth and progress. The tourist promotion organizations must verify if the HRD practices implemented in Madhya Pradesh guarantee employee loyalty and whether these practices foster employee happiness, as well as how employee satisfaction leads to employee engagement. The study examined the HRD procedures used by public sector tourist organizations in Madhya Pradesh, with the aim of identifying the specific techniques employed by these agencies. The study asserts that both employee happiness and employee engagement exert a substantial impact on enhancing employee loyalty. Therefore, the study corroborates the current literature that asserts a favorable correlation between employee happiness and employee loyalty. Similarly, the present study provides solid evidence for the beneficial impact of previous research on staff engagement including employee loyalty. Ultimately, the study validated the theoretical framework elucidating the correlation among HRD practices, employee happiness, employee engagement, and employee loyalty. This is achieved by analyzing the data using exploratory factor analysis, confirmatory factor analysis, and ultimately formulating structural equation modeling through hypothesis testing.